Abnormal expression of estrogen receptor is associated with thin endometrium. (3rd June 2019) - Gao, Mingxia; Cao, Chong; Zhang, Xuehong; Tang, Fabing; Zhao, Lihui; Luo, Sisi; Li, Lifei
Abstract: This study was conducted to investigate the association of estrogen receptor (ER) and progesterone receptor (PR) expressions with thin endometrium. Patients with endometrial thickness of less than 7 mm were classified as the study group, while the control group was comprised of patients with endometrial thickness of 7 to 14 mm. The expressions of ER and PR were detected with semi-quantitative immunohistochemical analysis, and the differences were compared between the two groups. The expression of ER was significantly decreased ( p  < .05) in the stromal cells of thin endometrium during both proliferative and secretory phases as compared to those of normal endometrium. Likewise, ER expression was found to be lower in the glandular cells of thin endometrium than those of normal endometrium during proliferative phase. However, no significant differences were observed for the expression of PR in both glandular and stromal cells between the two groups. Thin endometrium was associated with reduced expression of ER in stromal cells both during proliferative and secretory phase, but in glandular epithelial cells only during proliferative phase.